Increased Risk of Chronic Kidney Disease Associated With Weight Gain in Healthy Adults: Insight From Metabolic Profiles and Body Composition - Yun, Hae-Ryong; Kim, Hyung Woo; Chang, Tae Ik; Kang, Ea Wha; Joo, Young Su; Nam, Ki Heon; Kim, Hyoungnae; Park, Jung Tak; Yoo, Tae-Hyun; Kang, Shin-Wook; Han, Seung Hyeok (Frontiers in Medicine, 2021)
Objective: Obesity is an established risk factor for kidney damage. Here, we explored the long-term association of changes in body mass index (BMI) over time with incident CKD. Methods: 5393 middle-aged adults without comorbidities in the Korean Genome and Epidemiology Study were included in the analysis. Group-based trajectory modeling was used to determine the patterns of BMI change (decreasing, stable, and increasing BMI) between baseline and year 4. The primary outcome was the subsequent development of CKD from year 4. A multivariable Cox proportional hazards model was constructed to determine the risk of incident CKD according to BMI trajectories. Results: During 55 327 person-years, incident CKD occurred in 354 (6.5%) participants; 6.0, 6.1, and 7.8 per 1000 person-years across the trajectories, respectively (P=0.005). In multivariable-adjusted Cox proportional hazards model, the increasing BMI trajectory was associated with a 1.4-fold (hazard ratio [HR], 1.41; 95% confidence interval [CI], 1.06-1.87) higher risk of incident CKD compared with stable BMI trajectory. This association was stronger for the overweight and obese individuals. The HRs for CKD development in these two groups were 1.6 (95% CI, 1.06-1.87) and 2.2 (95% CI, 1.40-3.48), respectively. While the increasing BMI group was gaining weight, there were concomitant increases in blood pressure, insulin resistance, serum concentrations of total cholesterol, triglyceride, and hs-CRP, and fat mass, but HDL-cholesterol level and muscle-to-fat ratio decreased. Conclusion: Weight gain is associated with increased risk of incident CKD in healthy adults. This association is attributed to worsening metabolic profiles and increasing fat mass.